Influencia de la velocidad de enfriamiento sobre las propiedades estructurales de nanohilos de plata - Cuba Supanta, G. (2011)
In this paper we study the influence of cooling rate on the structural properties of silver nanowires with 1.6 nm of diameter. This study is done employing molecular dynamics methods with a tight-binding potential. The cooling rates used are in the range of 0.25-25 K/ps. The structural analysis of these systems is performed studying the pair correlation function and the pair analysis technique. The results indicate that the cooling rate affects significantly the structural properties of silver nanowires finding two representative rates, the rupture rate of 2.55 K/ps, where the nanowire is broken into two nanoparticles, and the collapse rate of 1.73 K/ps, where the two nanoparticles collapse to one spherical nanoparticle.